The Effect of Swiss Chard Powder and Starter Cultures on Color Development and Stability in Dry Cured Pork Loin - Silovska Nikolova, Aleksandra; Pejkovski, Zlatko; Belichovska, Daniela; Belichovska, Katerina (Faculty of Philology, University of Belgrade, 2023)
Dry meat products are highly demanded and valued in the market. When choosing them, the consumer, initially, notices their color. Nitrite is responsible for red-pinkish color development. Modern consumers are looking for processed meat with low contents of additives. The paper focuses on the influence of starter culture and Swiss chard powder added to dry cured pork loin on instrumentally measured L*, a*, b* values, as well as on product’s color stability at room temperature (20 ± 2°C), when the meat products were kept in normal daylight for a duration of up to 120 minutes. Five groups of cured pork loins were produced: I - Control (negative), using table salt and dextrose; II - Control (positive), using nitrite curing salt and dextrose; III - nitrite curing salt, dextrose and starter culture; IV - Swiss chard powder (first producer), dextrose and starter culture and V - Swiss chard powder (second producer), dextrose and starter culture. L*-values ranged between 28.42 (group III) and 34.23 (group I). The highest share of red color (10.86) was measured in group III. The share of yellow color ranges between 2.11 (group I) and 2.84 (group IV). Starter culture had a statistically significant (p£0.05) impact on color development and stability of cured pork loin produced with and without nitrite curing salt.
Keywords: dry cured loin, color quality, starter culture, nitrite, Swiss chard powder